Application of an enhanced device to transluminal retrieval of malappositioned coronary stents: An experimental study. (21st August 2017) - Mori, Masayuki; Sakata, Kenji; Yokawa, Junichiro; Nakanishi, Chiaki; Okada, Hirofumi; Shimojima, Masaya; Yoshida, Shohei; Yoshimuta, Tsuyoshi; Hayashi, Kenshi; Yamagishi, Masakazu; Kawashiri, Masa‐aki
Abstract : Objectives: This study investigated the application of a novel enhanced device to retrieval of deployed stents in a porcine coronary model. Background: Recurrence of in‐stent restenosis and stent thrombosis still remains to be resolved. Under these conditions, it is sometimes necessary to retrieve malfunctional stents responsible for thrombosis. However, few data exist regarding the feasibility and safety of retrieval device use in previously deployed coronary stents. Methods: We have developed an enhanced device consisting of an asymmetric forceps, conducting shaft (1.6 mm diameter, 150 cm length), and control handle. Bare‐metal stents (3 mm diameter) were implanted in four pigs to create a malapposition model. Coronary artery injury was evaluated by intravascular ultrasound (IVUS) and histological imaging on the first and 14th days. Results: The device was delivered to the coronary artery using the existing catheter (7 Fr). After opening the forceps, the blade was forced into the space between the vessel wall and the stent, and the stent struts were then grasped with the forceps. This was then pulled back into the catheter, still grasping the stent struts with the forceps. All stents were successfully retrieved by this method ( n = 4). On the first day, no apparent vessel wall injury was detectable by IVUS, although histological findings revealed damage to endothelial monolayer on retrieval of deployed stent. On the 14th day, mild intimal thickening was observed by IVUS and histology. Conclusions: These results demonstrate that the present device can be applied to transluminal retrieval of acquired malappositioned coronary stents.